A history and catalogue of the Lindsay Library, 1570-1792 the story of 'some bonie litle bookes' - Jackson Williams, Kelsey 1986-; Stevenson, Jane 1959-; Zachs, William (Brill, 2022)
This is the first study of Jacobean Scotland's largest library: the collection assembled over several generations by the Lindsays of Balcarres. It challenges prior understandings of pre-Union Scotland's book culture, presents the catalogue of a collection of international importance for the first time, and recovers the intellectual history behind this "Great Bibliotheck".0The volume includes chapters on the history of the library to the Restoration (Jane Stevenson) and from Restoration to Enlightenment (Kelsey Jackson Williams) as well as a detailed discussion of the library's reconstruction (William Zachs and Jackson Williams), a full catalogue, and appendices
Keywords: Lindsay -- Familie : Schottland; Geschichte 1570-1792; Privatbibliothek; Lindsay family / Library; Libraries / Scotland / History; Lindsay (Famille) / Bibliothèque; Bibliothèques / Écosse / Histoire; Lindsay family; Libraries; Scotland; History; Katalog